What Determines Financial Sustainability in Local Government? Evidence from Aceh Province, Indonesia - Syahriyal, Syahriyal; Abdullah, Syukriy; Meutia, Rita (Riset Akuntansi dan Keuangan Indonesia, 2023)
This research aims to determine the influence of financial independence, budget solvency, service solvency, population, and GRDP on local government financial sustainability. The results of this research are important to provide input for local governments in arranging appropriate policies to encourage financial sustainability. This research was conducted on 23 regional governments in Aceh by using the panel data regression analysis method with the assistance of the Eviews 12 version. The data was taken from the audited financial reports of regional governments in the 2017-2021 period. This research employed income surpluses in operational reports to measure regional government financial sustainability. The research results show that financial independence has no effect on financial sustainability, but budget solvency and service solvency have a significant positive effect. In contrast, population and GRDP have a negative effect on financial sustainability.